The Role of Industry Effects in Simultaneous Reversal and Momentum Patterns in One-Month Stock Returns. Issue 4 (1st October 2016) - Simpson, Marc W.; Grossman, Axel
ABSTRACT: When stocks are ranked by returns in one month, the portfolio of loser stocks tends to outperform the portfolio of winner stocks in the subsequent month. Yet industry portfolios tend to display momentum. We develop a model of information diffusion among agents with constrained information processing ability that reconciles these well-documented phenomena. We test whether this model or the overreaction hypothesis is consistent with the data. Additionally, a trading strategy based on the model outperforms strategies based on overreaction and on industry momentum. The strategy produces abnormal returns while controlling for market – risk and the size, book value, January, momentum, and liquidity effects.